1983
DOI: 10.1136/oem.40.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Knee degeneration in concrete reinforcement workers.

Abstract: The loads on the knees in concrete reinforcement work and maintenance painting were analysed on eight construction work sites. A total of 352 reinforcement workers and 231 painters, Finnish men aged 20-64, were clinically and radiologically examined to determine the condition of the knee joints in active workers. The loads on the knees and the occurrence of minor injuries and accidents were higher in reinforcement work than in painting, but the occurrence of symptoms, clinical signs, and radiological findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…There are only four earlier case-referent studies that have focused on the occupational risk factors of knee OA among women (14,(21)(22)(23). In two recently published studies, the cases were recruited in the same way as in our study, but the proportion of women was much lower, 60% (21) and 51% (22).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are only four earlier case-referent studies that have focused on the occupational risk factors of knee OA among women (14,(21)(22)(23). In two recently published studies, the cases were recruited in the same way as in our study, but the proportion of women was much lower, 60% (21) and 51% (22).…”
Section: Discussionmentioning
confidence: 98%
“…The etiology of knee OA is multifactorial, and the following risk factors have been identified: heredity (1-3), obesity (1,(4)(5)(6)(7)(8)(9)(10), injury (1,(7)(8)(11)(12) and physical loading (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Physical loading can be attributed to either occupational or recreational activities or both.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include two cohort studies, 21,33 five case-control studies, 11,13,37,40,44 and five cross-sectional studies. 17,18,23,28,42 Nine studies reported a positive relationship between knee OA and occupation (OR ¼ 1.4-4.7), 11,13,17,21,23,37,40,44 but only three scored high on methodological quality. 13,37,40 Many studies in this subgroup are older and have procedural flaws, such as failing to control for relevant covariates 17,21 or low participation rates.…”
Section: Occupational Groupsmentioning
confidence: 99%
“…[17][18][19]23,28,39,43 Twenty studies found a statistically significant relationship between occupational physical loading and knee OA (OR ¼ 1.4-7.9); of these, 13 received high quality scores. 9,13,14,19,25,26,29,31,34,37,39,40,43 All three cohort studies reported significant results for men.…”
Section: Occupational Physical Loading By Sexmentioning
confidence: 99%